Desempenho cognitivo e funcionalidade em idosos institucionalizados - Flores, Anderson (2019)
Human aging is a multidimensional phenomenon with a subjective character. It is influenced by factors such as genetic inheritance, lifestyle, socioeconomic and health-disease conditions, and others. The aging process may be accompanied by physiological or even pathological changes that may affect the cognition and functional capacity of the elderly and demand attention and care for these individuals. Cognitive and functional impairment are factors that lead to the search for long-term care institutions. Thus, these institutions receive elderly people with different conditions of functional and cognitive ability. These conditions are associated with several factors, such as history of past illness, access t o goods and services, education. The aim of this dissertation is to verify the prevalence and factors associated with cognitive and functional impairment in institutionalized elderly. This is a cross-sectional study conducted with 476 individuals aged 60 or over, male and female, residing in Homes for the Aged in the municipalities of Passo Fundo, Carazinho and Bento Gonçalves, in the state of Rio Grande do Sul. Data collection was performed by through a questionnaire including sociodemographic variables and health-related variables. The assessment of cognitive function was performed through Mini-Mental State Exam (MMSE). If the elderly were unable to respond to MMSE, the Clinical Dementia Rating was used. Functional capacity was assessed using the Katz Index and frailty using the Fried Phenotype. This study was approved by the Research Ethics Committee of the University of Passo Fundo, according to the Consubstantiated Opinion no. 2.097.278. All participants signed the Informed Consent Form. This research generated two scientific productions. The first, entitled “Cognitive decline and associated factors in institutionaliz ed elderly: a cross-sectional study”, identified a prevalence of cognitive decline in 73.3% of the study population. Factors associated (p<0.05) with the outcome investigated were: not being literate, being dependent on Basic Activities of Daily Living, no n-fragile and pre-fragile condition, having chronic pain. The second production, entitled “Functional dependence in institutionalized elderly and associated factors”, identified functional dependence present in 85.1% of the elderly, presenting as associated factors (p<0.05) to this dependence: cognitive decline, sarcopenia, urinary incontinence and advanced age were also associated with functional capacity. These results highlight the need for a systematic evaluation to monitor the cognitive and functional conditions of institutionalized elderly in order to qualify care, especially in the context of institutionalization, and promote the quality of life of this population.